Answered

Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

Solve [tex]\sqrt{-6x + 19} = x - 2[/tex]. Check for extraneous solutions.

A. [tex]x = -5[/tex]
B. No solution
C. [tex]x = -5, 3[/tex]
D. [tex]x = 3[/tex]


Sagot :

To solve the equation [tex]\( \sqrt{-6x + 19} = x - 2 \)[/tex] and check for extraneous solutions, follow these steps:

### Step 1: Isolate the radical
Given:
[tex]\[ \sqrt{-6x + 19} = x - 2 \][/tex]

### Step 2: Square both sides to eliminate the square root
[tex]\[ (\sqrt{-6x + 19})^2 = (x - 2)^2 \][/tex]

This simplifies to:
[tex]\[ -6x + 19 = (x - 2)^2 \][/tex]

### Step 3: Expand and simplify the quadratic equation
Expand the right-hand side:
[tex]\[ -6x + 19 = x^2 - 4x + 4 \][/tex]

Rearrange all terms to one side to set the equation to zero:
[tex]\[ x^2 - 4x + 4 + 6x - 19 = 0 \][/tex]
[tex]\[ x^2 + 2x - 15 = 0 \][/tex]

### Step 4: Factor the quadratic equation
Factorize the quadratic equation:
[tex]\[ (x + 5)(x - 3) = 0 \][/tex]

### Step 5: Solve for [tex]\( x \)[/tex]
Set each factor to zero and solve for [tex]\( x \)[/tex]:
[tex]\[ x + 5 = 0 \quad \text{or} \quad x - 3 = 0 \][/tex]
[tex]\[ x = -5 \quad \text{or} \quad x = 3 \][/tex]

### Step 6: Check each solution for extraneous solutions
We need to substitute [tex]\( x \)[/tex] back into the original equation to ensure they are not extraneous solutions.

#### Check [tex]\( x = -5 \)[/tex]
Substitute [tex]\( x = -5 \)[/tex] into the original equation:
[tex]\[ \sqrt{-6(-5) + 19} = -5 - 2 \][/tex]
[tex]\[ \sqrt{30 + 19} = -7 \][/tex]
[tex]\[ \sqrt{49} = -7 \][/tex]
[tex]\[ 7 \neq -7 \][/tex]

Since [tex]\( \sqrt{49} = 7 \)[/tex] does not equal [tex]\(-7\)[/tex], [tex]\( x = -5 \)[/tex] is an extraneous solution.

#### Check [tex]\( x = 3 \)[/tex]
Substitute [tex]\( x = 3 \)[/tex] into the original equation:
[tex]\[ \sqrt{-6(3) + 19} = 3 - 2 \][/tex]
[tex]\[ \sqrt{-18 + 19} = 1 \][/tex]
[tex]\[ \sqrt{1} = 1 \][/tex]
[tex]\[ 1 = 1 \][/tex]

Since both sides are equal, [tex]\( x = 3 \)[/tex] is a valid solution.

### Conclusion
The only valid solution is:
[tex]\[ \boxed{3} \][/tex]
Thus, the correct answer is:
D. [tex]\( x = 3 \)[/tex]